Influence of incubation temperature on emu (dromaius novaehollandiae) egg hatchability - KUMAR, P SENTHIL; JAGATHEESAN, P N RICHARD; ANANDH, M ANNA; RAJARAJAN, G; PARAMASIVAM, A (The Indian Journal of Animal Sciences, 2012)
The study was conducted to assess an effect of incubation temperature (97.5° F, 98.0° F and 98.5° F) on hatching performance of emu eggs. A total of 150 eggs were divided into 3 equal groups (1, 2 and 3) differing in the incubation temperature (97.5° F, 98.0° F and 98.5° F in dry bulb respectively). Significant differences between the groups were observed for dead in shell. Raising the temperature to 98°F in G 2 and 98.5° F in G 3 led to reduce hatchability indices, primarily due to an increased rate of embryonic mortality found in both groups. Significantly different (P